"Shoulder pain and limitation of motion in a young girl: think different" - Matteo Trevisan; Luca Di Lenarda; Serena Pastore; Alessia Saccari; Gianluca Canton; Umberto Lucangelo; Andrea Taddio; Luigi Murena (BMC, 2022)
Abstract Background Primary Synovial Chondromatosis (PSC) is a rare benign tumor of the synovial membrane in which cartilage metaplasia produces calcific loose bodies within the articular space. Only a few cases are reported in the pediatric population and its etiology remains unknown. This condition typically affects large weight-bearing joints with pain, swelling and decrease range of motion. Due to its slow progressions, delayed diagnosis is frequent and differential diagnosis should consider other chronic arthritis and malignancies. While arthroscopic removal of loose bodies is the current treatment up to now, the association of partial or complete synovectomy is debated. Case presentation We report about a 14-year-old girl with a long-lasting right shoulder pain, especially during movements or exercise, localized tenderness and hypotonia of the glenohumeral joint. No previous trauma was mentioned. Blood exams, Mantoux test and plain radiography of the right shoulder were unremarkable. Ultrasound imaging revealed echogenic and calcified bodies stretching the glenohumeral joint and dislocating the long head of biceps tendon. Magnetic resonance showed a "rice-grain" pattern of the right shoulder. From an arthroscopic surgery, multiple loose white bodies were removed within the synovial membrane, and synovial chondromatosis was confirmed by histological analysis. At one month follow up visit, the patient completely recovered without pain. Conclusion Synovial chondromatosis is a very uncommon cause of mono articular pain in children, especially when it affects shoulder. Pediatricians should keep in mind this condition to avoid delayed diagnosis and treatment, even in consideration of the low risk of malignant transformation. Through this case, we would highlight common diagnostic pitfalls and treatment of synovial chondromatosis.